Pengaruh FDR, NPF, dan CAR terhadap Profitabilitas Bank Syariah (Studi Kasus PT Bank BTPN Syariah Tbk. Periode Tahun 2019-2022) - Kamilah, Assa'adatul (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The development and growth of sharia-based banking and financial institutions in Indonesia from year to year shows an improved performance, as well as its contribution to the national economy has increased significantly. Banks that are well managed can provide benefits that will increase profitability. This study aims to examine the effect of FDR, NPF, and CAR simultaneously and significantly on Profitability by using the ROA ratio at PT Bank BTPN Syariah Tbk. Period 2019-2022. By using processing techniques and power analysis in the form of multiple linear regression with the t test, F test, and the coefficient of determination. The research results show that partially the FDR, NPF, and CAR variables have no significant effect on profitability (ROA). Simultaneously the independent variables (FDR, NPF, and CAR) have no effect on profitability (ROA).